(untitled) (World Bulletin of Education and Learning, 2025)
This article explores the historical formation and developmental stages of Uzbek traditional performance and vocal art. As one of the most significant expressions of national spirituality and aesthetic thought, music has always reflected the cultural memory and emotional world of the Uzbek people. The study examines the origins of musical performance in ancient rituals and labor songs, the theoretical and aesthetic essence of performance as a creative triad between composer, performer, and listener, as well as the evolution of vocal art through folklore, maqom, and classical singing traditions. Particular attention is given to the role of ’hofizlik’ — the art of the master performer — which represents the highest stage of professional and spiritual mastery in Uzbek music. The paper also analyzes the continuity of this art in modern times, where young performers preserve classical traditions while adapting them to contemporary interpretations. The research emphasizes the importance of preserving hofizlik as a vital element of Uzbekistan’s intangible cultural heritage and a means of transmitting national identity and musical philosophy to future generations.